Go green in architecture - Siddiquee, Tahir Abdul Rahman; Abdullah, Fadzidah; Sanusi, Aliyah Nur Zafirah; Hasan, Mohd Khalil (2019)
The term "Go Green" is a widely used term having a wide variety of meanings depending on who uses it. Going green may be perceived in three simple steps "conserve energy, reduce pollution and save money" in our day to day chorus. More you achieve them, more you are going green. It may also be the way of life in which individuals are conscious of how their activities are affecting the environment? Clean and green environment is the key requirement of quality life. An architect’s responsibility is to train himself and to educate his clients to apply the principles of go green in designing and construction of buildings i.e. minimal use of energy that too from low-cost environment-friendly non-conventional sources of energy with energy harvesting ideas in operation and selective use of the low-cost environment-friendly materials in construction. These two are the major factors in controlling environmental pollution. The use of green construction materials, green energy resources and principles of green architecture will lead to the green buildings. In this presentation, the authors will discuss the different green energy resources, green construction materials and the green architectural strategies to construct green buildings for sustainability and quality life.